Forward shoulder posture in collegiate swimmers: A comparative analysis of muscle-energy techniques - Laudner, K. G.; Wenig, M.; Selkow, N. M.; Williams, J.; Post, E. (Journal of Athletic Training, 2015)
Context: Empirical data for treating forward shoulder posture supports stretching the anterior shoulder musculature. Although muscle-energy techniques (METs) have been hypothesized to lengthen muscle, no data have described the usefulness of this technique among swimmers.